i am also slightly confused about this.
Follow Math Help Forum on Facebook and Google+
Using $\displaystyle z=e^{it}$ : $\displaystyle \displaystyle\int_{\Gamma}z^mz^n\;dz=\ldots=i\disp laystyle\int_0^{2\pi}e^{(m+n+1)it}\;dt=\ldots$
thank you so much. from that i get. i[(m+n+1)2(pi)ie^((m+n+1)2(pi)i)] is that correct?
Originally Posted by shaheen7 thank you so much. from that i get. i[(m+n+1)2(pi)ie^((m+n+1)2(pi)i)] is that correct? It's hard to understand what you really meant, but it should be $\displaystyle \displaystyle{i\int\limits^{2\pi}_0e^{(m+n+1)it}\, dt=\frac{1}{m+n+1}e^{(m+n+1)it}\left|\limits^{2\pi }_0\right.$ . Now distinguish between $\displaystyle m+n\neq -1\mbox{ and }m+n=-1$ Tonio
righttt that is what i was doing i just made a small mistake. THANK YOU!